2010
DOI: 10.1002/smll.201000032
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Aspects of Long‐Term Treatment of Keratinocytes with ZnO and TiO2 Nanoparticles

Abstract: Sunscreens containing ZnO and TiO(2) nanoparticles (NPs) are increasingly applied to skin over long time periods to reduce the risk of skin cancer. However, long-term toxicological studies of NPs are very sparse. The in vitro toxicity of ZnO and TiO(2) NPs on keratinocytes over short- and long-term applications is reported. The effects studied are intracellular formation of radicals, alterations in cell morphology, mitochondrial activity, and cell-cycle distribution. Cellular response depends on the type of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(134 citation statements)
references
References 34 publications
8
119
2
1
Order By: Relevance
“…The nano-sized ZnO was found more cytotoxic than the micrometer-sized ZnO with LC 50 values of 15 ± 1 and 29 ± 4 lg, respectively [41]. Prolonged exposure to ZnO nanoparticles at 10 lg ml results in decreased mitochondrial activity, loss of normal cell morphology, and disturbances in cell cycle distribution [42]. A-375 cells were studied for the comparative morphology of untreated and treated ZnO nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The nano-sized ZnO was found more cytotoxic than the micrometer-sized ZnO with LC 50 values of 15 ± 1 and 29 ± 4 lg, respectively [41]. Prolonged exposure to ZnO nanoparticles at 10 lg ml results in decreased mitochondrial activity, loss of normal cell morphology, and disturbances in cell cycle distribution [42]. A-375 cells were studied for the comparative morphology of untreated and treated ZnO nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…41 The NPs were only found inside vesicles within the cytoplasm, particularly in early and late endosomes and amphisomes. Moreover, exposure resulted in ROS generation, decreased mitochondrial activity, loss of normal cell morphology, and a disturbed cellcycle distribution.…”
Section: In Vitro Studies Using Dermal Cell Linesmentioning
confidence: 99%
“…11,14,15 The characteristics of ZnO NPs, the dose, the treatment time, and the specific cell line selected may affect the results obtained. 48,51 The data presented here showed that the cell cycle was arrested at the G2/M phase after treatment with 50 µg/mL of 100 nm ZnO NPs for 24 hours (Figure 2C), suggesting that the HaCaT cells exposed to ZnO NPs were unable to go through mitosis, leading to the subsequent decreased cell viability at 48 hours.…”
Section: Expression Of Apoptosis-related Genes Was Upregulated In Hacmentioning
confidence: 99%
“…10 Long-term exposure to ZnO NPs has been reported to stimulate the generation of ROS, initiating death processes and affecting the cell cycle distribution. 11 ZnO NPs may inhibit cell growth by reducing proliferation. 12,13 Reduced proliferation has been linked to cell cycle arrest at various phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation